Quality assurance and long-term stability of a novel 3-in-1 X-ray system for brachytherapy - Karius, Andre; Szkitsak, Juliane; Boronikolas, Vasilios; Fietkau, Rainer; Bert, Christoph (Journal of Applied Clinical Medical Physics, 2022)
Purpose A novel, mobile 3-in-1 X-ray system featuring radiography, fluoroscopy, and cone-beam computed tomography (CBCT) has been launched for brachytherapy recently. Currently, there is no quality assurance (QA) procedure explicitly applicable to this system equipped with innovative technologies such as dynamic jaws and motorized lasers. We developed a dedicated QA procedure and, based on its performance for a duration of 6 months, provide an assessment of the device's stability over time. Methods With the developed QA procedure, we assessed the system's planar and CBCT-imaging performance by investigating geometric accuracy, CT-number stability, contrast-noise-ratio, uniformity, spatial resolution, low-contrast detectability, dynamic range, and X-ray exposure using dedicated phantoms. Furthermore, we evaluated geometric stability by using the flexmap-approach and investigated the device's laser- and jaw-positioning accuracy with an in-house test phantom. CBCT- and planar-imaging protocols for pelvis, breast, and abdomen imaging were examined. Results Planar- and CBCT-imaging performances were widely stable with a geometric accuracy <= 1 mm, CT-number stability of up to 46 HU, and uniformity variations of up to 48 HU over time. For planar imaging, low-contrast detectability and dynamic range exceeded current recommendations. Although geometric stability was considered tolerable, partly substantial positioning inaccuracies of up to more than 120 mm and -13 mm were obtained for lasers and jaws, respectively. X-ray exposure showed small variations of <= 0.56 mu Gy and <= 0.76 mGy for planar- and CBCT-imaging, respectively. The conductance of the QA procedure allowed a smooth evaluation of the system's overall performance. Conclusion We developed a QA workflow for a novel 3-in-1 X-ray system allowing to assess the device's imaging and hardware performance. The system showed in general a reasonable imaging performance and stability over time, whereas improvements regarding laser and jaw accuracy are strictly required.
CRIS-Team WoS Importer:2022-07-29